Characteristics of 22 nm UTBB-FDSOI technology with an ultra-wide temperature range. (1st October 2022) - Wang, Hanbin; Bi, Jinshun; Bu, Jianhui; Liu, Hainan; Zhao, Fazhan; Cao, Huajun; Ai, Chao
Abstract: The performance of the ultra-thin body and buried oxide fully-depleted silicon-on-insulator metal-oxide-semiconductor field-effect-transistors based on a 22 nm technology node is investigated in this paper over an ultra-wide temperature range from 6 K to 550 K. The current–voltage ( I – V ) characteristics under wide temperature range conditions are shown, including the influence of the back-gate bias ( V bg ). The important electrical parameters, such as threshold voltage ( V t ), subthreshold swing, ON-state current ( I on ), and OFF-state current ( I off ), are extracted with temperature changes. From 550 K to 6 K, V t increased by 0.21 V, I off decreased nearly six orders of magnitude, and the gate-induced drain leakage current decreased by nearly eight orders of magnitude. The main physical mechanisms for the changing electrical performance with temperature are the variation of carrier concentration, mobility, and energy band. By utilizing a technology computer-aided design simulation, the temperature dependence of the device performance is discussed and analyzed.